THE PRINCIPLE OF EQUALITY ACCORDING TO CUSTOMARY LAW - Velçani , Majlinda (International Journal of Legal and Social Order, 2025)
The purpose of this paper is to summarize the concepts of customary law and analyze how international customary law functions and how the principle of equality is conceived in customary law. For many centuries in the absence of written constitutions and constitutional laws, the norms which regulated state and social activity were customary norms. Repeated over time and continuously, they had the 'legal' power in a certain territory. Customary law is defined as the set of customs, practices and beliefs that are accepted as mandatory rules of conduct by a community. These practices or rules were also used to regulate relations between different states. Even today, customary law is one of sources of law, in cases where we have legal gaps. What is one of the most delicate issues in social arrangements under the influence of customary law is inequality and discrimination against women. This inequality under the influence of customary law still occurs in different countries of the world. Initially, during the work, the definitions of customary law will be given, continuing further with customary international law. One of the important issues to be elaborated is customary law in Albania and how equality and discrimination are under the influence of the norms of of customary law.